'Overworked and underappreciated': special education teachers describe stress and attrition. Issue 3 (26th May 2020) - Hester, Olivia R.; Bridges, Shannon A.; Rollins, Lauren Hart
ABSTRACT: Rising attrition rates and the shortage of highly qualified special education teachers have a negative impact on students and school districts. This study explores the open-ended questions that were part of a larger mixed-method analysis to uncover the voices of current special education teachers ( n = 366) from across the United States. Using their own words, teachers identify work-related stressors and express their reasonings behind leaving the field of special education. Overall, results indicate that teachers did not feel supported by their administrators and that their profession had an adverse effect on their overall quality of life, thereby contributing to feelings of burnout. Recommendations for future research and the need for professional development are discussed.